Performance evaluation of potato clones for the central Terai Region of Nepal - Gotame, Tek Prasad; Poudel, Sujata; Thapa, Bihani; Neupane, Janaki Datta (Journal of Agriculture and Natural Resources, 2021)
A series of experiments were carried out to evaluate the performance of exotic potato clones including PRP lines at research field of Regional Agricultural Research Station (RARS), Parwanipur, Bara, Nepal during the winter seasons of 2017 and 2018. Thirty-nine potato clones were evaluated in initial evaluation trial and eleven clones were evaluated in coordinated varietal trial with check varieties Khumal Ujjwal and Kufri Jyoti. From the initial varietal trial in 2017, the highest tuber yield (21.54 mt/ha) was found in CIP389660.9 followed by CIP391046.14 (21.38 mt/ha). In 2018, the highest tuber yield (29.72 mt/ha) was produced in CIP392759.1 followed by CIP393085.5 (26.92 mt/ha) and CIP391046.14 (26.64 mt/ha). In 2018, the tuber yield was the highest (26.12 mt/ha) in PRP 266265.15 followed by CIP 393371.159 (24.79 mt/ha). In coordinated varietal trial carried out in 2017/18, the highest tuber yield was noted in CIP394600.52 (42.65 mt/ha) followed by CIP395443.103 (30.83 mt/ha) and CIP395445.16 (24.43 mt/ha) respectively. Whereas in 2018/19, the highest yield was produced by PRP266265.15 (26.12 mt/ha) followed by CIP393371.159 (24.79 mt/ha) and CIP 396012.266 (22.66 mt/ha) respectively. In RARS, Parwanipur conditions, CIP 394600.52, CIP 395443.103, CIP 395445.16 and CIP 304394.56 along with PRP 266265.15 were found to be superior to standard check variety. These potential genotypes need to be further verified in farmers field in additional districts of central Terai region before notifying in the national seed system. Adoption of these clones as variety may increase the potato production and improve the food, and nutritional security in the central Terai region of Nepal.